Revisiting Word-initial Glottal Stops in Persian: Underlying or Epenthetic? - Ali Pirhayati (مطالعات زبان‌‌ها و گویش‌های غرب ایران)
The phonological status of word-initial glottal stops in Persian has been a subject of controversy. Particularly, researchers hold divergent views on whether the glottal stop functions as a phoneme in word-initial positions. These perspectives can be categorized into three main positions: (1) glottal stops are phonemes in all occurrences (Samareh, 1985; Windfuhr, 1979); (2) word-initial glottal stops are phonemes only in loanwords, especially from Arabic (Bijankhan, 2018; Haghshenas, 1991; Jam, 2019; Kord-Zaferanloo-Kambozia, 2003); and (3) word-initial glottal stops are not phonemes in Persian (Jahani, 2005; Majidi & Ternes, 1999; Sepanta, 1973). In this paper, a critical review of previous findings is provided along with new insights and neglected evidence relevant to the underlying representations of words with glottal stops. Based on these considerations, the paper leans towards the position that glottal stops function as phonemes in all positions regardless of occurrence in loanwords or native words. It also calls for a revision of previous research, emphasizing the importance of non-acoustic aspects in exploring the phonological functions of word-initial glottal stops.